Factors Influencing the Choice of a Public or Private Health Institution for Childbirth in Chandigarh - Khumukcham, Trusty; Singh, Tarundeep; Kaur, Manmeet; Gupta, Madhu; Kumar, Rajesh (Indian Journal of Community Health, 2015)
Background: Knowledge of factors affecting the choice of place for delivery may help in developing a user friendly maternity program. Hence, this study aimed at finding out factors influencing women’s choice about the type of health institutions for delivery. Materials and methods: A cross sectional study was conducted in selected communities of Chandigarh city in India during 2010-11. A consecutive sample of 300 women (150 in public and 150 in private institutions) who had delivered a baby in previous three months were interviewed using a pre-tested interview schedule. Chi square test was used to find association of socio-demographic, maternal, and institutional factors with the type of institution selected for delivery. Results: Women from lower socio-economic status delivered more frequently in public sector institutions (47.3%) than in private institutions (16.7%) (p<0.01). In private institutions 30% of the women were delivered through Caesarean Section compared to 17.3% in public institutions (p<0.05). Physical infrastructure was better in private institutions. Cost was lower in public (Rs. 4,630) than in private institutions (Rs 21,676). Most women were satisfied with quality of care received in public and private institutions. However, some reported that public institution staff needs to be more polite. Quality of infrastructure in health facility, quality of care, and socio-economic status were associated with the choice of institution for delivery. Conclusions: Public sector health institutions are a major source of maternity care in Chandigarh, hence, care providers should be trained in handling clients gently. Regulations for adherence to protocols, e.g., indications for Caesarean Section and fee structure etc. need to be implemented in private institutions.